Biocompatibility of quantum dots (CdSe/ZnS ) in human amniotic membrane-derived mesenchymal stem cells in vitro - Wang, Gongping; Zeng, Guangwei; Wang, Caie; Wang, Huasheng; Yang, Bo; Guan, Fangxia; Li, Dongpeng; Feng, Xiaoshan (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2015)
BACKGROUND AND AIM: Amniotic membrane-derived mesenchymal stem cells (hAM-dMSCs) are a potential source of mesenchymal stem cells which could be used to repair skin damage. The use of mesenchymal stem cells to repair skin damage requires safe, effective and biocompatible agents to evaluate the effectiveness of the result. Quantum dots (QDs) composed of CdSe/ZnS are semiconductor nanocrystals with broad excitation and narrow emission spectra, which have been considered as a new chemical and fluorescent substance for non-invasively labeling different cells in vitro and in vivo. This study investigated the cytotoxic effects of QDs on hAM-dMSCs at different times following labeling. METHODS: Using 0.75, 1.5 and 3.0 μL between quantum dots, labeled human amniotic mesenchymal stem cells were collected on days 1, 2 and 4 and observed morphological changes, performed an MTT cell growth assay and flow cytometry for mesenchymal stem cells molecular markers. RESULTS: Quantum dot concentration 0.75 μg/mL labeled under a fluorescence microscope, cell morphology was observed, The MTT assay showed cells in the proliferative phase. Flow cytometry expression CD29, CD31, CD34, CD44, CD90, CD105 and CD106. CONCLUSIONS: Within a certain range of concentrations between quantum dots labeled human amniotic mesenchymal stem cells has good biocompatibility.
Keywords: human amniotic membrane; testování materiálů; fluorescenční mikroskopie; Materials Testing; techniky in vitro; Biological Assay; kvantové tečky; amnion; biotest; Quantum Dots; mesenchymal stem cells; biocompatibility; lidé; biokompatibilní materiály; Microscopy, Fluorescence; Humans; barvení a značení; Amnion; quantum dots; Staining and Labeling; Mesenchymal Stem Cells; Biocompatible Materials; In Vitro Techniques; mezenchymální kmenové buňky